"We Dissect Stupidity and Respond to It": Response Videos and Networked Harassment on YouTube. (May 2021) - Lewis, Rebecca; Marwick, Alice E.; Partin, William Clyde
Over the past decade YouTube "response videos" in which a user offers counterarguments to a video uploaded by another user have become popular among political creators. While creators often frame response videos as debates, those targeted assert that they function as vehicles for harassment from the creator and their networked audience. Platform policies, which base moderation decisions on individual pieces of content rather than the relationship between videos and audience behavior, may therefore fail to address networked harassment. We analyze the relationship between amplification and harassment through qualitative content analysis of 15 response videos. We argue that response videos often provide a blueprint for harassment that shows both why the target is wrong and why harassment would be justified. Creators use argumentative tactics to portray themselves as defenders of enlightened public discourse and their targets as irrational and immoral. This positioning is misleading, given that creators interpellate the viewer as part of a networked audience with shared moral values that the target violates. Our analysis also finds that networked audiences act on that blueprint through the social affordances of YouTube, which we frame as harassment affordances. We argue that YouTube's current policies are insufficient for addressing harassment that relies on amplification and networked audiences.